2015
DOI: 10.2485/jhtb.24.241
|View full text |Cite
|
Sign up to set email alerts
|

A New Anterior and Posterior Maxillary Expansion Index in Orthodontics via Digital Dental Models

Abstract: The aim of this study was to determine the maxillary expansion index (MEI) for Pakistani population. Also to determine the sexual disparities in sum of incisors perimeter, arch width and expansion indices of maxillary arch. Hirox digital stereomicroscope was used for the fabrication of the digital models. The estimated sample size was 128 Pakistanis (64 females and 64 males; age range from18 -24 years). The perimeters of the maxillary permanent incisors, as well as intercanine, interpremolar, and intermolar ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These findings are in agreement with those of Nimkarn et al, 9 who found an over-estimation of arch widths estimated by Pont's index relative to actual arch width measured on dental casts. 3 On the other hand, Alam et al, 6 found an under-estimation of the dental arch width.Pont index should not be extrapolated to individuals of different ethnic origins as it does not give accurate estimates of ideal arch widths for a given individual in the majority of cases. 10 The reasons that may explain the lack of applicability of the index in the studied population may be due to the dental size or the amplitude of the arch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in agreement with those of Nimkarn et al, 9 who found an over-estimation of arch widths estimated by Pont's index relative to actual arch width measured on dental casts. 3 On the other hand, Alam et al, 6 found an under-estimation of the dental arch width.Pont index should not be extrapolated to individuals of different ethnic origins as it does not give accurate estimates of ideal arch widths for a given individual in the majority of cases. 10 The reasons that may explain the lack of applicability of the index in the studied population may be due to the dental size or the amplitude of the arch.…”
Section: Discussionmentioning
confidence: 99%
“…A digital slide calipers (Mitutoyo, Japan) with sharpened beaks was used to measure the mesiodistal crown diameters of the maxillary permanent incisors and arch widths on the dental casts, to an accuracy of 0.1mm. 3,5 The mesiodistal crown diameter of the tooth was measured from anatomical contact point of one tooth to another on the occlusal side perpendicular to the long axis of the teeth. In those instances where there was slight attrition, the measuring point for arch width was determined as the middle of the facet on the tooth.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the mesiodistal width of the teeth in males and females were the same at certain ages. Shahid et al [8] in 2015 reported that only the size of maxillary lateral incisors, canines, and first premolars and mandibular lateral incisors was significantly different in the right and left quadrants. Considering the gap of information regarding the tooth size and arch size in an Iranian population, the existing controversy in this regard, and the significance of this topic in orthodontic and prosthodontic treatments, and forensic medicine, study of tooth size and arch size in an Iranian population is a necessity.…”
Section: Introductionmentioning
confidence: 99%